Epigenetic odyssey to decrypt the hidden code for sustainable brassica production: enhancing yield, stress resilience and nutritional quality - Maithreyi, R. Shubhra; Preet, Sugyan; Tanwar, Kunal; Chakraborty, Puja; Gupta, Isha; Verma, Rachana; Bharti, Jyotsna; Thangaraj, Arulprakash; Kaul, Rashmi; Kaul, Tanushri (Frontiers in Plant Science, 2026)
High demand for agricultural products together with the changing climate imposes an urgency for improving crop productivity and quality. The Brassica family has evolved as a globally significant oilseed crop due to its multifaceted application for edible oils, seed meals, and biodiesel production. However, its wide-scale crop production is limited due to the advent of several external stressors. Development of resilient Brassica crops requires recognition of the chromatin state complexes to fine tune the transcriptional machinery. Epigenetic modification through DNA methylation, histone modification, RNA directed gene silencing, and chromatin remodeling plays a major role in modulating flowering time, gametogenesis, embryogenesis, seed development and whole genome duplication to shape key agronomical traits. In conjunction, recent progress in the field of sequencing technologies and genome editing have led to the characterization of key epigenetic markers for identifying crucial agronomic traits and subsequent molecular designing. Therefore, the current review details the mechanism and application of the recent epigenetic approaches that have contributed for the generation of climate-smart Brassica family.